London in his own time : a biographical chronicle of his life, drawn from recollections, interviews, and memoirs by family, friends, and associates - Reesman, Jeanne Campbell (Writers in their own time, 2020)
"Everyone knows Jack London for his tales of adventure in Alaska and the Canadian Yukon. With his work translated into more than 100 languages, London is one of the most popular American writers in the world, alongside Mark Twain. Yet for the reader tackling The Call of the Wild or White Fang, or perhaps his most often-anthologized short story "To Build a Fire," many misconceptions about his life confuse his legacy. London in His Own Time is based on Jeanne Reesman's nearly thirty-five years of archival research. The book offers some surprising perspectives on Jack London's many sides by family, friends, fellow struggling young writers, business associates, high school and college mates, interviewers, editors, coauthors, visitors to his Sonoma Valley Beauty Ranch in Glen Ellen, California, and more. People who have commented on and discussed the mercurial genius include Joseph Conrad, Theodore Dreiser, Upton Sinclair, Sinclair Lewis, Ambrose Bierce, and Mary Austin, as well as his half-sister, Eliza London Shepard, and his first wife, Elizabeth Bess "Bessie" Maddern London. There are a few Klondike pals he kept in touch with, and some fellow writers such as Cloudesley Johns, but many of those closest to him truly demonstrate his wide range of friends: barman Johnny Heinold; his second wife, Charmian, whom he called "Mate Woman"; his daughters; his lover, Anna Strunsky; his closest friends, especially the poet George Sterling; his former crewmate on the Snark, Martin Johnson; and his valet/memoirist, Yoshimatsu Nakata. Reesman also includes dozens of entries from Bay-area socialists, friends in Hawai'i and the South Seas, fellow war correspondents, neighbors like Luther Burbank, and his long-time editor at Macmillan, George Brett. Reesman's curated book reveals the humor and sense of fun that brought London's friends and family members together, but also share the poignant, thoughtful, and tragic moments as well"--